PENGEMBANGAN MEDIA 3D HOLOGRAM PADA MATERI KEADAAN CUACA DI KELAS III YPI ANNUR PRIMA - Suci Triyana Daulay; Nuri Ramadhan; Syarifah Ainun Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to develop a learning medium based on 3D hologram technology for weather conditions material in the third grade of elementary school. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of the study involved material experts, media experts, a classroom teacher, and 32 third-grade students. The instruments used included expert validation questionnaires, student response questionnaires, and media effectiveness tests. The results showed that the 3D hologram media on weather material was assessed as highly feasible by both material and media experts. The effectiveness test showed scores of 74% (teachers) and 89% (students), both categorized as very good. Thus, the 3D hologram media can serve as an innovative learning tool to improve students’ understanding of science concepts in elementary schools.